O28. Optimization of Lu-177 SPECT/CT acquisition protocol at Tygerberg Hospital Nuclear Medicine Department. (September 2016) - Mkhize, T.; Moalosi, T.; Mix, M.; Ellmann, A.; Nolan, L.
Abstract : Introduction: 177 Lu is a radionuclide which is used for the treatment of the neuroendocrine tumours, bone pain from metastatic disease, and prostate cancer. 177 Lu has two prominent gamma energies of 113 and 208 keV (6.8% and 10.4% yield) used for imaging, and a therapeutic beta energy of 0.5 MeV. In this work, we investigated ways in which we can reduce the time needed to scan patients by varying time per view and optimizing image reconstruction without compromising on the image quality for dosimetry. Materials and methods: A 10 litre image quality phantom (NEMA2007/IEC2008) was scanned using a GE Infinia Hawkeye1 gamma camera to acquire SPECT/CT images using the old and new protocol. The phantom was filled with an activity concentration of 45 kBq/ml as background, and the spheres 383 kBq/ml. The phantom was scanned using a time per view of 15 sec, 20 sec and 30 sec for each projection (120 in total). Activity concentration was determined for each scan and total scan time evaluated. The scans were acquired, using a MEGP collimator with 128 × 128 matrix size and a 208 keV only energy peak was selected. All scans were reconstructed with the same parameters using OSEM, and an experienced Nuclear Medicine physician was requested to rank the reconstructed scans using individual visual qualitative assessment. Results: It was determined that the 15 sec time per view protocol scored well in comparison with our old 30 sec protocol, this allowed us to be able to reduce the scan time from 40 min to 25 min (15 min reduction). Conclusion: Patient scan time was reduced (reducing motion errors) and camera scan time improved in the department (resulting in more scans fitting in the schedule than previously).